Translating the Qurʾān into Indonesian Languages - Riddell, Peter G. (Al-Bayān, 2014)
The rendering of the Qur’anic text into other languages is a matter of considerable sensitivity and debate, given the status of the text among the community of faithful as divine speech. This article considers this issue in the context of the Malay-Indonesian world, where Islam has been firmly established since the beginning of the 14th century. Discussion initially focuses upon surviving evidence of Qur’anic materials from the early Islamic period in Southeast Asia. Attention then turns to the rendering of the Qurʾān into the Malay/Indonesian language, according to three periods up to the 21st century. The article concludes with a discussion of translation of the Qurʾān into the regional languages of Indonesia.